Cara Belajar Siswa Berprestasi Kelas III di MI Ma’arif Depokrejo Pasca Pandemi - Indah Styowati; Agus Nur Soleh; Nadia Raifah Nawa Kartika (IAINU Kebumen, 2022)
The purposes of this research is to describethe way students learn achievers in class III atMI Ma’arif Depokrejo. This research is a qualitative research with a descriptive research design.The research subjects were third grade teachers at MI Ma’arif Depokrejo and the fourth gradestudents of Islamic Primary School of Ma’arif (MI Ma’arif) Depokrejo their parents. The methodused in this research is a qualitative method which includes interviews, observation, anddocumentation. The data collected is in the form of data, namely the learning method ofoutstanding students. The data analysis technique used includes three stages, namely datareduction, data presentation, and drawing conclusions. The results showed that students' learningmethods were such as, studying hars, doing assignments, arranging study schedules, makingmaterial summaries, paying attention to the learning process, understanding and memorizinglessons